Evaluation of self-esteem in hearing aid and cochlear implant users - AKDENİZ, ESRA (My University, 2022)
© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.Purpose: We investigated the relationship between hearing aid or cochlear implant use and self-esteem, quality of life, hearing quality, and speech perception. Methods: Of the 120 participants studied, 29 were cochlear implant users, 26 were hearing aid users, 33 were non-device users with hearing loss, and 32 had normal hearing. Each individual included in the study WHOQOL–BREF Quality-of-Life Scale, Rosenberg Self-Esteem and Speech, Spatial Perception and Qualities of Hearing Scale was applied. Results: We found that the self-esteem level of the group with hearing loss, but without a device, was significantly lower than that of the group with a cochlear implant/hearing aid. There was a moderately statistically significant relationship between self-esteem, quality of life, speech perception, and hearing quality. Conclusions: Using hearing aid and cochlear implants increases self-esteem among people with hearing impairments. Self-esteem is associated with quality of life, speech perception, and hearing quality.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KULAK BURUN BOĞAZ; Clinical Medicine (MED); CLINICAL MEDICINE; OTORHINOLARYNGOLOGY; Otorhinolaryngology; Cochlear implant; Hearing aid; Hearing loss; Quality of life; Self-esteem; Self-esteem · Quality of life · Hearing loss · Hearing aid · Cochlear implant